2007
DOI: 10.1111/j.1572-0241.2007.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Combined Evaluation of the Serum Adiponectin Level, HOMA-IR, and Serum Type IV Collagen 7S Level to Predict the Early Stage of Nonalcoholic Steatohepatitis

Abstract: Approximately 90% of the patients with early-stage NASH can be predicted by a combined evaluation of the serum adiponectin level, HOMA-IR, and serum type IV collagen 7S level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 37 publications
3
73
0
6
Order By: Relevance
“…Specifically, adiponectin signalling alleviated or prevented NASH in mice, 33,34 and associations of hypoadiponectinaemia with fatty liver and/or NASH have been reported in humans. 35,36 Furthermore, genetic studies revealed associations of ADIPOR1/2 with IR and liver fat content, 37,38 and overexpression of ADIPOR1/2 has been shown to potentiate subeffective doses of adiponectin. 39 We therefore suggest that the increased ADIPOR1/2 mRNA expression in obese, insulin-resistant subjects represents a mechanism that may partially compensate for reduced plasma adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, adiponectin signalling alleviated or prevented NASH in mice, 33,34 and associations of hypoadiponectinaemia with fatty liver and/or NASH have been reported in humans. 35,36 Furthermore, genetic studies revealed associations of ADIPOR1/2 with IR and liver fat content, 37,38 and overexpression of ADIPOR1/2 has been shown to potentiate subeffective doses of adiponectin. 39 We therefore suggest that the increased ADIPOR1/2 mRNA expression in obese, insulin-resistant subjects represents a mechanism that may partially compensate for reduced plasma adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 36.2% of nonobese patients with NAFLD were diagnosed as having NASH. Also, several studies have shown that BMI is not a useful independent factor for differentiating NAFL from NASH in Japanese patients with NAFLD [6,19,20]. Based on these perspectives, an accurate tool for differentiating NAFL from NASH would be needed even in nonobese patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…CK-18 is an intracellular protein mainly produced by necrosis and apoptosis of cells of epithelial origin including hepatocytes, and is a useful serum biomarker that reflects cell death [26]. Recently, serum CK-18M65 released in NAFLD patients in the process of the cellular death has been proposed as a possible serum biomarker of NASH [27,28]. The increased serum levels of CK-18 fragments, in some clinical cohorts of obese patients or those with insulin resistance, are associated with hepatocyte injury, inflammation and fibrosis [29.…”
Section: Discussionmentioning
confidence: 99%